A8.5 Baricitinib effects on serum cholesterol and circulating lipid particles in a phase 2B study in patients with rheumatoid arthritis. (13th February 2015) - Kremer, J; Genovese, MC; Keystone, E; Taylor, P; Zuckerman, SH; Schlichting, DE; Beattie, SD; Macias, WL
Abstract : Background: Baricitinib, a novel oral JAK1/2-inhibitor, was evaluated in a Phase 2b study in patients with moderate-to-severe RA. The primary ACR20 12-week-endpoint was met, and maintained through 24 weeks. 1 Objective: To evaluate changes in serum LDL, HDL, and total cholesterol over 24 weeks of baricitinib treatment compared with placebo. Methods: Patients were randomised to QD dosing with placebo (n = 98) or 1, 2, 4, or 8 mg of baricitinib with ˜50 patients per treatment arm. Serum lipids were determined at screening, baseline and at Weeks 2, 4, 8, 12, 14, 16, 20, 24, and particle size and number were determined by Nuclear Magnetic Resonance (NMR) at baseline, Weeks 12/24. Results: Baricitinib treatment resulted in dose- and time-dependent increase relative to placebo in LDL, HDL and total cholesterol detectable by Week-2. The mean percent increase in total cholesterol in the combined baricitinib arms was 9.5% (p < 0.001) at Week-12 and 11.3% by Week-24. LDL-cholesterol increased 10.5% (p < 0.001) in combined baricitinib arms at Week-12 and 13.7% by Week -24, HDL-cholesterol increased 11.8% (p = 0.004) and 13.4% respectively. While the magnitude of increase in HDL-cholesterol correlated with reductions in C-reactive protein observed at week-12, no similar correlation was noted for the increase in LDL-cholesterol. NMR-analysis revealed significant changes in baricitinib-treated groups relative to placebo in the size (LDL) and number (HDL, VLDL) of particles by Week-12 that were sustained at 24 weeks. The increase in LDL-cholesterol was associated with an increase primarily in the large LDL particles, which was significant at all baricitinib doses. Large LDL in the combined baricitinib arms (N = 203) had a mean value of 486 nmol/L at Week-0 which increased to 539 nmol/L at Week-12 (p = 0.001) and to 564 nmol/L at Week-24 (N = 154). No significant increases in small, medium small, or very small LDL-particles, or in total number of LDL-particles in any of the treatment arms were observed. An increase in HDL (10.3%, p = 0.006) and VLDL (28.7%, p = 0.074) particle numbers was apparent at Week-12 in the combined baricitinib arms which persisted to Week-24 with no significant increases in the mean particle size for HDL or VLDL through 24 weeks. While this analysis reflects pooled doses, the effects on lipids were most marked at 8 mg QD. Conclusions: The increase in LDL-cholesterol with baricitinib treatment is attributed to a shift towards larger particles rather than an overall increase in LDL-particle number at Week-12 and persisting through 24 weeks, while changes observed in HDL-cholesterol were associated with an increase in total number of HDL-particles. 1 Reference: Genovese MC, Keystone E, Taylor P, et al . Arthritis Rheum 2012; 64 :2487.